PENGARUH MODEL PEMBELAJARAN ASSURANCE RELEVANCE INTEREST ASSESSMENT AND SATISFACTION TERHADAP PENINGKATAN HASIL BELAJAR FLUIDA STATIK SISWA KELAS XI SMAN 1 INDRALAYA - Reny .; Murniati .; Ketang Wiyono (JURNAL INOVASI DAN PEMBELAJARAN FISIKA, 2014)
The purpose of this study was to observe the effect of learning model Assurance, Relevance, Interest, Assessment, and Satisfaction (ARIAS) on student learning outcomes in static fluid material. The method used in this study is the method of quasi-experimental design with nonequivalent control group design. The population of this entire class XI Science SMAN 1 Indralaya and this sample is a class XI Science 1 as an experimental class and class XI Science 2 as the control class in the second semester of school year 2013-2014. Data collection techniques used were tests and observation. The test is used to see the results of student learning and observation sheet to see the feasibility ARIAS learning models and the activities of students. The results of this study the data obtained experimentally class N-gain of 0.68 (medium category) and N-gain control class 0.27 (low category). Data resulting from adherence to the model ARIAS observation sheet shows the percentage of 85% in the first meeting and continued to increase to 100% until the last meeting. Activities of students at the first meeting by 33% and showed an increase up to the last meeting reached an average percentage of 95%. Statistical test results showed that there is a significant influence on the learning model ARIAS student learning outcomes. It can be concluded that the increased activity of the experimental class students learn through application of learning models ARIAS exert significant influence on learning outcomes of students in the experimental class than the control class.